(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
Music, like other art forms, shows different aspects of life through images. The basis of the content of musical images is the inner feelings of the first person, his feelings, and his feelings. They occupy the main place in musical images. It is also found in descriptive and musical works. In music, sound imitation is a way of depicting pictures and images of events occurring in the listener’s mind, before their eyes. A musical work lives in time and during this time changes the mental state of a person in his inner feelings, feelings, and thoughts, influencing his subtle feelings. Based on this, this article discusses the importance of spiritual and aesthetic education of young people through musical art.